Patient Satisfaction Following Intrathecal Targeted Drug Delivery for Benign Chronic Pain: Results of a Single‐Center Survey Study - Schultz, David M. (Neuromodulation, 2020)
OBJECTIVES: Targeted Drug Delivery (TDD) is commonly used for the management of patients with intractable pain. Past studies have proven efficacy in pain relief and reduction in opioid use and cost‐effectiveness in long‐term pain management. There are few studies investigating satisfaction among patients with implanted pain pumps that are managed with targeted intrathecal medications. MATERIAL AND METHODS: Patients in a single medical practice implanted with pain pumps for relief of intractable pain were identified and extracted from the electronic health record (EHR). Six hundred and ten active TDD patients were identified and an anonymous 18‐question survey was administered to determine satisfaction with TDD therapy. During an 18‐month period from May 2018 to August 2019, patients were invited to take a satisfaction survey. Both primary and secondary outcomes were reported as proportions; P < 0.05 was considered significant. RESULTS: Four hundred and forty‐three patients (74% of the active pump population) completed the survey. The majority of patients reported improvement in pain, improvement of physical function, improvement in quality of life and reduction in opioid use. Complete discontinuation of oral opioid intake was reported in 38.9% of patients. The majority of patients had a 40 cc reservoir implanted in an upper buttock pocket site and overall, 91% of patients were happy with pump pocket location. CONCLUSION: Intrathecal TDD therapy can relieve pain and improve quality of life in patients with intractable pain and offers a reasonable alternative to long‐term oral or skin patch opioid management. Patients utilizing TDD therapy reported high degrees of satisfaction.